Identifikasi Single Nucleotide Polymorphism (SNP) Gen Thrombospondin-related Anonymous Protein (TRAP) Pada Penderita Malaria falciparum di Wilayah Kerja Puskesmas Hanura, Kabupaten Pesawaran, Provinsi Lampung - Muhammad Irfan Adi Shulhan Muhammad Irfan Adi Shulhan (Yayasan Pendidikan Medika Indonesia, 2022)
Malaria is a disease caused by the Plasmodium parasite in erythrocytes as evidenced by positive microscopic examination, there are antigens, and the discovery of Deoxyribo Nucleid Acid / Ribonucleid Acid (DNA / RNA) Plasmodium parasite on Polymerase Chain Reaction (PCR). Plasmodium falciparum is one of the most deadly species of malaria, and there are many genes that support this parasite to infect, so there are so many genetic variations produced by one gene. This type of research uses a survey research design with descriptive method. The study sample was obtained from 18 Stored Archived Biological Materials (ABM). This research was conducted using the PCR method which was analyzed by gel electrophoresis and continued to the sequencing method to detect genetic variations of the Plasmodium falciparum Thrombospondin-related anonymous protein (PfTRAP) gene. There were 18 samples that had been carried out nested PCR, then obtained variations in the length of the band in each sample. There are single nucleotide polymorphism in the Thrombospondin-related anonymous protein (TRAP) gene